Toponímia de Comunidades Indígenas do Município de Pacaraima - Araújo, Maria do Socorro Melo (2014)
The toponymy, in Brazil, has been showing if a rich field of research inside of the names studies, sees your objectives they surpass the naming act, to reconstitute values partner-historical, cultural and linguistic, and to reveal episodes of diferente moments from the community's existence. The study concerning Toponymy of Indigenous Communities of the Municipal district of Pacaraima broke of the hypothesis that the toponymies in Portuguese Language bring in the underlay, at least, a toponymy in indigenous language that is revealed by the study of the etymology and of the linguistic strata. The dissertation analyzed lines historical-cultural, linguistic and etymologic of the indigenous communities' names and we tried to understand what it took a people to baptize themselves with certain toponymy, what was important for that denomination and if the community had received previous toponymies, as well as understanding what might have caused the substitution of a toponymy for other. The corpus was constituted of 27 human accidents, indigenous communities of Pacaraima, in Indigenous land São Marcos and the Raposa Serra do Sol. The work was orientated, mainly, for the theoretical-methodological parameters of Dick (1990, 1992, 2000). The dissertation showed that the motivation toponymic goes back mainly to the fauna, the flora and culture of the area, for example Guariba, Banana plantation and Maruai respectively. While the investigation of the etymology of the presented phrases, as decisive, the simple formula, SN(N), ‘Surumu’, although they appear some complex of the type SN(SN + Posp(+ Cóp)) ‘wa’rara’pise’ (TR), and it organized the toponymies in four groups, considering your former elements: the) Toponymies in LP with correspondent in LI, b) Toponymies in LP without correspondent in LI, c) Toponymies in LI with correspondent in the LP and d) Toponymies in LI that they suffered ‘aportuguesamento’. In this picture, the largest occurrence is in the item " a " of the classification and the smallest in the item " b ". The study evidenced, in the classification of the taxonomy, Zootoponymies, Fitotoponymies and Ergotoponymies. Finally, it ratified the reach of the oral narratives in the rebuilding of the memory and of the communities' history, in the same way it proved the presence of underlying languages to the current toponymies in Portuguese.